DEVELOPMENT OF A SOFTWARE MODULE FOR OPERATIONAL DISPATCH CONTROL OF PRODUCTION BASED ON CYBER-PHYSICAL CONTROL SYSTEMS - Igor Nevliudov; Vladyslav Yevsieiev; Nataliia Demska; Sergiy Novoselov (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject of research in the article is production management processes based on cyber-physical systems. The purpose of the work is to automate the management of production processes using the cybernetic component and analyze the results. To achieve this goal, it is necessary to solve the following tasks: develop an analytical and logical model of the CPPS development management process taking into account the requirements specified in the terms of reference for the development CPPS; to present the analytical and logical structure of connections in the form of a model of interaction of the main windows and all the necessary graphical elements for the implementation of the full-featured interface of the developed CPPS; to carry out experimental researches of efficiency and practical approbation of the received theoretical results, by comparison of classical methods and the developed ones. Results: The targets, physical and cybernetic components of the CPPS development management process were combined in a single information space from the beginning of development to its implementation. The process of checking the achievement of the main goal of CPPS development has been automated, which makes it possible to make changes and manage the CPPS development process at any level and stage of the proposed technology. The process of managing the development of the cybernetic component is automated on the basis of synthesized algorithms of functioning using the GUI elements of object-oriented programming languages, which made it possible to increase the flexibility of the proposed architecture and technologies for automating the CPPS development process and to reduce the development time of the cybernetic component. Conclusions: the proposed models and methods will not only automate the process of managing the development of CPPS from scratch, but will also make it possible to automate the process of managing the development of the cybernetic component for the modernization and improvement of existing CPPS.